PENERAPAN PROMOSI DENGAN MEDIA SOSIAL PADA UMKM KUE MOCI “NAJAH” DI KOTA SEMARANG - Yani, Tri Endang; Wibisono, Totok; Roestanto, Anantya (Fokus ABDIMAS, 2023)
The "Najah" moci cake business is one of the MSMEs affected by the Covid-19 pandemic, where its business has experienced a decline. After the Covid-19 pandemic subsides in 2022, these MSMEs are starting to try to get back on their feet. However, sales results were not as expected. The small amount of sales of this moci product could be due to the fact that this product is not well known by the public. So far, activities to introduce products to the public or promotions have not been carried out. Therefore, it is very important for MSMEs to carry out promotional activities so that they are known to the wider community. This Community Service aims to help MSMEs in promotional activities via sosial media so that they can support the success of their business. The method for implementing community service activities is the training and mentoring method. After carrying out community service, there has been a positive change in the "Najah" moci cake MSME actors, where MSME actors can carry out promotional activities through sosial media, especially Facebook and Instagram. Keywords: Covid-19, Moci Cake, Sosial Media, Promotion, MSMEs